Hubungan Pola Asuh Ibu Dalam Pemberian Makan Pada Balita Dengan Kejadian Stunting Di Desa IV Koto Setingkai tahun 2023 - Sari, Putri Julisma; Harahap, Dewi Anggriani; Erlinawati, Erlinawati (Evidence Midwifery Journal, 2024)
The implementation of maternal parenting regarding the provision of balanced nutritional food plays a very important role in children's growth and development. The aim of this research was to determine the relationship between maternal parenting patterns in feeding toddlers and the incidence of stunting in Village IV Koto Setingkai, the UPT work area. Lipat Kain Community Health Center in 2023. This research is an analytical study with a cross sectional design. The population in this study were all parents who had toddlers aged 12-60 months in IV Koto Setingkai Village, the working area of ??the Lipat Kain Community Health Center, namely 130 toddlers. The sample in this study was 130 toddlers using a total sampling technique. The data collection tool uses a questionnaire sheet. Data analysis in this study used univariate and bivariate analysis. The results of the research on maternal parenting patterns in feeding toddlers in the democratic parenting category were 97 (76.4%) respondents and 115 (88.5%) respondents were toddlers who did not experience stunting. The results of statistical tests showed that there was a relationship between maternal parenting in feeding toddlers and the incidence of stunting with a p-value (0.000). The conclusion is that there is a relationship between maternal parenting patterns in feeding toddlers and the incidence of stunting in IV Koto Setingkai village, the UPT work area. Lipat Kain Health Center in 2023. It is hoped that mothers of toddlers will always pay attention to fulfilling their children's nutrition. Fulfillment of nutrition is based on four key messages, including eating a variety of foods, a clean and healthy lifestyle, an active lifestyle and exercise, and regularly monitoring the child's weight and height.